Diagnosing chronic hand eczema by an algorithm: a tool for classification in clinical practice - Molin, Sonja; Diepgen, Thomas L.; Ruzicka, T.; Prinz, J. C. (Clinical and experimental dermatology, 2011)
Background. Diagnostic classification of chronic hand eczema (CHE) represents a major clinical and taxonomic challenge because of its wide aetiological and clinical heterogeneity. Aim. To develop an algorithm for the diagnosis and classification of CHE. Methods. Well-defined aetiological, clinical and morphological criteria of CHE were arranged graphically in a diagnostic hierarchy, and validated in 137 German patients with hand eczema. Results. The algorithm distinguished chronic hand eczema due to contact allergy, irritant damage or a combination of the two, each either with or without atopy, and also atopic hand eczema and idiopathic hand eczema lacking obvious causative factors. Foot involvement helped to distinguish idiopathic from irritant hand eczema. Each subtype could occur either with a hyperkeratotic-rhagadiform, dyshidrotic or mixed morphology, but certain hand eczema subtypes had clear morphological preferences. Conclusions. By providing a more precise clinical definition this diagnostic algorithm could improve the classification and taxonomy of hand eczema subtypes, facilitating more rational treatment decisions and allowing better treatment outcome analysis.
Gesehen am 01.09.2022